2012
DOI: 10.1177/0095244311420530
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between fresh and exposed swelling elastomer

Abstract: Last decade has seen growing use of swelling elastomers in various applications by the oil and gas industry. Elastomers with special properties have been developed to sustain the specific downhole conditions of temperature, pressure, and chemical environment in different wells. Apart from targeted short-term tests conducted by rubber developers and drilling application companies, little is known about material characterization of such elastomers. Even these test results are not generally available in the publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
(18 reference statements)
2
18
0
1
Order By: Relevance
“…12,13 Study on vulcanization kinetics, ageing in water and thermal degradation behavior of EPDM insulator have also been reported. [14][15][16][17][18][19][20][21][22] Extensive studies are reported on characterization/performance of EPDM insulation reinforced with glass micro balloons, Boron, Borax and Kynol fiber. [23][24][25][26] Studies on EPDM/NBR blend, maleated EPDM are also reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 Study on vulcanization kinetics, ageing in water and thermal degradation behavior of EPDM insulator have also been reported. [14][15][16][17][18][19][20][21][22] Extensive studies are reported on characterization/performance of EPDM insulation reinforced with glass micro balloons, Boron, Borax and Kynol fiber. [23][24][25][26] Studies on EPDM/NBR blend, maleated EPDM are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Literature is available on improving the interface bonding properties of EPDM insulator to propellant by incorporating and varying the concentration of CSE and HTPB based bonding agent and weakening of bond strength by absorbed water 12,13 . Study on vulcanization kinetics, ageing in water and thermal degradation behavior of EPDM insulator have also been reported 14‐22 . Extensive studies are reported on characterization/performance of EPDM insulation reinforced with glass micro balloons, Boron, Borax and Kynol fiber 23‐26 .…”
Section: Introductionmentioning
confidence: 99%
“…Addition of hydrophilic fillers (usually sodium polyacrylate and polyethylene glycol) is needed to make inert elastomers swellable such as ethylene propylene rubbers (EPDM), hydrogenated nitrile rubbers (HNBR), and so on. [1][2][3] Swelling elastomer is sometimes also treated as a gel, which is an aggregate form of elastomer swollen by immersion into the solvent. Swelling elastomers or gels have a variety of applications in biological engineering, micro fluidics, and petroleum industry.…”
Section: Introductionmentioning
confidence: 99%
“…Swelling results in change of geometry, density, hardness and other properties. [1][2][3][4] Water-swelling elastomers swell through the absorption of saline water following the mechanism of osmosis, while oil-swelling elastomers swell by the absorption of hydrocarbons through a diffusion process. 5,6 Swelling rate depends on the temperature, pressure, type of elastomer and fluid composition.…”
Section: Introductionmentioning
confidence: 99%